Edukasi Penggunaan Suplemen Kesehatan yang Rasional di Samarinda - Niken Indriyanti; Fahriani Istiqamah Jafar; Fika Aryati (Jurnal Pengabdian Masyarakat (abdira), 2022)
A phenomena increased use of health supplement in Samarinda community is lasting since COVID-19 pandemic. The people knowledge about health supplement consumption a are dominantly received from advertisement and published article on internet. However, not all of the informations are correct. Therefore, this community service program was a webinar and interactive discussion about the use of health supplement, in a zoom meeting media. The pretest and post test were used to evaluate the benefit of this program.  From a total of 67 participants, 37 of them fill the pretest form, and 28 fill the posttest form. As many as 92% of participants believe that health supplements keeps body healthy, and 43% of them routinely consumed health supplements. After our explanation and discussion session, 86% participants stated that very much new information they received, ang 50% of them said that their way to use health supplement were not fully correct. As many as 93% participants satisfied to this community service program. It can be concluded that this education program was successful.